Allergic Rhinitis- An Updated Review for Healthcare Professionals - Sadruddien , Aisha Abdulaziz; Alotaibi , Abdulkarim Awadh Mashan; M. Alsulami, Saif Saud; Al-Mazini, Abdul Aziz Ahmed Zuhayyan; Alobaid, Sultan Salman Ibrahim; Alotaibi, Turki Muhayya; Alrowais, Khaled Abdulrahman Khaled; Alotaibi , Ahmed Traheeb B; Alotaibi , Salman Mahmas F; Al-Qahtani, Ziad Nasser Ali; Faqih, Homud Ali; Alotebe, Faisal Tarehib; et al. (Journal of Ecohumanism, 2024)
Background: Allergic rhinitis (AR) is an immunoglobulin E (IgE)-mediated condition characterized by nasal symptoms such as congestion, sneezing, rhinorrhea, and itching. It is prevalent globally, affecting about 15% of the population, and can significantly impact quality of life, productivity, and healthcare costs. Historically considered a localized disorder, AR is now recognized as part of a broader systemic allergic framework. The condition is categorized into seasonal, perennial, or mixed forms. Effective management relies on identifying triggers and applying appropriate pharmacologic and non-pharmacologic interventions. Aim: This review aims to provide an updated understanding of the etiology, epidemiology, diagnostic approach, and treatment strategies for AR, with a focus on practical management for healthcare professionals. Methods: A comprehensive review of current literature on allergic rhinitis, including pathophysiology, risk factors, diagnostic approaches, and treatment options. The article discusses pharmacologic therapies (e.g., corticosteroids, antihistamines), immunotherapy, and lifestyle modifications. Results: AR pathogenesis involves both early-phase IgE-mediated responses and late-phase inflammatory processes. Environmental, genetic, and lifestyle factors influence AR prevalence. The condition affects different age groups, with seasonal forms more common in children and perennial in adults. A combination of avoidance measures, pharmacotherapy (intranasal corticosteroids, antihistamines), and allergen immunotherapy remains central to management. Emerging treatments like monoclonal antibodies (omalizumab) have shown promise for severe cases. Personalized management strategies are crucial, given the variability in treatment responses. Conclusion: Allergic rhinitis is a common condition with substantial personal and societal impact. Effective management involves a comprehensive approach that includes identifying and avoiding triggers, using appropriate medications, and considering advanced therapies for severe cases. With individualized treatment plans, healthcare professionals can optimize patient outcomes and reduce the burden of AR.